Secondary School Students' Participation in Sports and their Parents' Level of Support: A Qualitative Study - Maniam Vegneskumar (Sciendo, 2017)
The study investigated student involvement in sports as part of co-curricular activities in the school and outside, and the effect of parental support upon their child's participation in sport. The purpose of the study was to investigate in-depth the views of year 11 students from six Australian schools about their parents' influence on their participation in sport. The schools agreed to allow their students to participate on a voluntary basis. The primary data were gathered from 111 students in the form of written personal statements in response to the researcher's open-ended guideline questions, based on the humanistic sociological approach of studying respondents' personal perspectives on a particular phenomenon. The 80% of respondents who claimed to play sport were involved in a total of 23 different sports, with soccer being the most frequently mentioned (29%). The 20% of respondents who did not play sport all attended schools where participation in sport was not compulsory. Parental support for sports participation was evident in 89% of their comments, but only 11% of parents played an active role. The negative family constraints identified by 15% of respondents referred to issues such as lack of parental interest in sport, concerns about safety, maintaining a balance between sport and other areas of life, and the cost involved